Regiodivergent Metal-Catalyzed Rearrangement of 3-Iminocyclopropenes into N-Fused Heterocycles - Chuprakov, Stepan (2007)
[Image: see text] A highly efficient regiodivergent method for the synthesis of N-fused heterocycles via transition-metal-catalyzed rearrangement of 3-iminocyclopropenes has been developed.